2019
DOI: 10.18488/journal.70.2019.64.213.223
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Benefits of Grain Legume Fallow Systems on Soil Fertility and Farmers Livelihood in the Humid Forest Zone of Cameroon

Abstract: Soil fertility management of smallholder farms in the humid tropics is a major issue as a result of inherently low fertility with nitrogen being the most limiting plant nutrient. Use of grain legume fallows could improve soil quality through nitrogen fixation and ensure food and nutritional security in developing countries. This field trial was laid out in a Randomized Complete Block Design (RCBD) to evaluate the short-term benefits of grain legume fallows (common bean, groundnut, cowpea, and soybean) on soil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 34 publications
(40 reference statements)
0
6
0
Order By: Relevance
“…The nutrient supply, such as nitrogen, is greater in improved fallow than in cropped land as the plants store nutrients from the air and bottomless layers of the soil, and falls their leaf litter to improve the soil and preserve moisture (Lemage and Tsegaye, 2020). Nanganoa et al (2019) indicated that different legume fallow systems had variable effects on the soil physicochemical properties of which the maximum distinguished effect is the total nitrogen content (ranging from 0.19 to 0.24%), organic carbon (SOC) content (ranging from 2.77 to 3.36%), and available phosphorus (ranging from 12.50 to 16.12 mg/kg) (Table 4).…”
Section: Improved Legume Fallowsmentioning
confidence: 99%
See 3 more Smart Citations
“…The nutrient supply, such as nitrogen, is greater in improved fallow than in cropped land as the plants store nutrients from the air and bottomless layers of the soil, and falls their leaf litter to improve the soil and preserve moisture (Lemage and Tsegaye, 2020). Nanganoa et al (2019) indicated that different legume fallow systems had variable effects on the soil physicochemical properties of which the maximum distinguished effect is the total nitrogen content (ranging from 0.19 to 0.24%), organic carbon (SOC) content (ranging from 2.77 to 3.36%), and available phosphorus (ranging from 12.50 to 16.12 mg/kg) (Table 4).…”
Section: Improved Legume Fallowsmentioning
confidence: 99%
“…Lemage and Tsegaye (2020) showed that abandoned agricultural land can be rehabilitated using improved legume fallow, which can enhance soil pH, organic carbon, available phosphorus, available potassium, and total nitrogen content. Besides this, Nanganoa et al (2019) indicated that different legume fallow systems had varying grain yield and economic benefits, ranging from enhanced soil nutrient contents, increased grain yield, and increased economic value of the fallow land. The authors revealed that grain yield ranging from 1.0 to1.9 t/ha can be obtained using different legume fallow systems with the highest in groundnut (1.9 t/ha), followed by soybean (1.6 t/ha), common bean (1.3 t/ha), and cowpea (1.0 t/ha) (Figure 4).…”
Section: Improved Legume Fallowsmentioning
confidence: 99%
See 2 more Smart Citations
“…Phaseolus vulgaris is an annual selfpollinated crop that belongs to the family of Fabaceae [5,6] and domesticated in Mesoamerica and Andes about 7000 years ago [5]. In developing countries common bean is very important in the nutrition of an increasing population where they deliver a fairly cheaper source of protein in the diet [7], fodder for animals [8] and source of elements for plant nutrition are the other benefits of common beans [9,10].…”
Section: Introductionmentioning
confidence: 99%